Ellis Van-Creveld Syndrome in an Ethnic Group in Nepal: Case Report with Review of Literature - Gauchan, Eva; Sharma, Prakash (Journal of Nepal Paediatric Society, 2016)
Ellis van-Creveld syndrome is a rare autosomal recessive disorder characterized by acromesomelic dwarfism, postaxial polydactyly, oro-dental abnormalities and congenital heart disease. We are reporting three cases in two families of the same ethnic group from Western Nepal. Genetic testing should be done in this population in order to identify the mutation in the gene causing the syndrome. J Nepal Paediatr Soc 2016;36(2):188-192.